LABOR PROBLEMS OF GENDER VICTIMS: COMPETENTIAL AND LEGAL (Acta Judicial Journal, 2021)
The protection of the victim of gender violence in Spanish law extends to the workplace. However, and despite these protections and regulations, the truth is that there is a labor problem for the victims of gender, unresolved, and consisting of competency and legal imbalances in relation to their labor rights. Non-compliance by, above all, the Administration and the assignment of powers to defend them, are other aspects not adequately resolved by the regulations and that must be addressed and reviewed to adapt their development to the cardinal needs of the victims.
Keywords: Victims of gender, labor rights, Spanish law